INTEGRASI PENANAMAN NILAI KRISTIANI MELALUI KEGIATAN PRAMUKA TERHADAP KECEERDASAN EMOSIONAL DAN PRILAKU PROSOSIAL PESERTRA DIDIK - Johni Hardori; Yuel Sumarno; Purim Marbun; Debora Elim (Bethel Press, 2023)
This study investigates the integration of Christian values through Scout activities and its influence on students’ emotional intelligence and prosocial behavior. Employing a quantitative correlational design, the research involved junior high school students who actively participated in Scout programs embedded with Christian teachings. Data were collected through Likert-scale questionnaires measuring the levels of value integration, emotional intelligence (self-awareness, self-regulation, motivation, empathy, and social skills), and prosocial behavior (helping, caring, and cooperation). The findings reveal that the integration of Christian values in Scout activities positively correlates with students’ emotional intelligence. Students who consistently engaged in value-based Scout practices demonstrated higher scores in emotional regulation and empathy. Furthermore, emotional intelligence was identified as a mediating factor that strengthened the relationship between value integration and prosocial behavior. Students with higher emotional intelligence exhibited greater willingness to help peers, cooperate in group tasks, and participate in community services. These results highlight the importance of integrating spiritual-ethical values in extracurricular activities as a holistic approach to character formation. Scout activities not only enhance technical and leadership skills but also foster emotional growth and moral motivation, enabling students to act prosocially as an expression of faith and service to others.